Incidences of Primary Soft Tissue Sarcoma Diagnosed on Extremities and Trunk Wall: A Population-Based Study in Taiwan. Issue 41 (October 2015) - Hung, Giun-Yi; Yen, Chueh-Chuan; Horng, Jiun-Lin; Liu, Chun-Yu; Chen, Wei-Ming; Chen, Tain-Hsiung; Liu, Chien-Lin
Abstract : Abstract: Most epidemiological studies of soft tissue sarcoma (STS) were performed in the Western countries, and only limited data highlighting that in the Asian population. The aim of this study is to conduct a comprehensive analysis for the incidence rates of STS in Taiwan. This was a population-based study analyzing the incidence rates and trends of the primary STS over extremities and trunk wall during 2003 to 2011 by using the nationwide Taiwan Cancer Registry. More specific analyses were conducted for subtypes. Incidence rates of overall STS by cities and counties were also investigated. A total of 3843 cases were diagnosed with STS during the study period, giving an age-standardized rate (ASR) of 1.63 per 100, 000 person-years. Liposarcoma was the most frequent subtype, followed by undifferentiated pleomorphic sarcoma and leiomyosarcoma. STS was more frequently diagnosed in males and angiosarcoma was the most prominent sex-specific type. ASR increased with age in most of the STS subtypes and varied by histologic subtype. The incidence of peripheral primitive neuroectodermal tumor was highest in children, whereas rhabdomyosarcoma revealed a bimodal age distribution. Annual percent change (APC) of STS was 2.2%, and significant change in trend was only in males (APC, 3.5%, P  < 0.05). Geographical variations indicated that New Taipei City had a significantly higher rate compared with the rest areas. Significantly lower rates were observed in 1 major offshore island. Incidence variations of STS by sexes, ages, histologic subtypes, and geographic regions were observed in Taiwanese population. The emerging factors associated STS incidence rates deserve further studies to verify.